CARDIOLOGY AND NEUROLOGICAL DISEASES ASSOCIATED WITH PSYCHOLOGICAL FACTORS: A CLINICAL APPROACH - Mahsudov Valijon Gafurjonovich (TADQIQOTLAR, 2026)
Abstract: This work is devoted to the study of the clinical approach to cardiological and neurological diseases associated with psychological factors. The study analyzes the impact of psychological states such as stress, anxiety, depression and emotional stress on the functioning of the cardiovascular and nervous systems. It is shown that psychological factors play an important role in the development of pathologies such as arterial hypertension, ischemic heart disease, arrhythmias, headaches, migraines and neuroses through psychosomatic mechanisms . The clinical approach emphasizes the need for a comprehensive assessment of patients, that is, a joint analysis of the somatic and psychological state. It also highlights the effectiveness of early diagnosis, psychotherapeutic approaches, pharmacological treatment and preventive measures. In general, the integration of the areas of psychocardiology and neuropsychiatry is of great importance in modern medicine.